Analisa Hubungan Antara Size, Product Life Cycle, Dan Market Position Dengan Penggunaan Balance Scorecard Pada Sektor Industri Restoran - Limanto, Kevin (Business Accounting Review, 2013)
With the Balanced Scorecard, restaurant entrepreneur can measure the performance of the restaurant entirely, not only the financial performance, but also the non-financial performance. The purpose of this study was to determine the relationship of organization size, product life cycle and market position against the use of the Balanced Scorecard in the restaurant industry in Surabaya. From the results of Pearson product moment correlation analysis researcher concluded that there was a significant positive relationship among organization size, product life cycle, and market position and the use of the Balanced Scorecard in the restaurant industry in Surabaya. This proved that the restaurant business in Surabaya has the perception that large restaurants, restaurants whose products are in the introduction or growth stage, as well as restaurants that have strong market position, that tend to implement the Balanced Scorecard in their business activities. The biggest perception of Balance Scorecard at restaurant industry is at the financial perspective.